Barriers to completing oral glucose tolerance testing in women at risk of gestational diabetes. Issue 9 (18th March 2020) - Lachmann, E. H.; Fox, R. A.; Dennison, R. A.; Usher‐Smith, J. A.; Meek, C. L.; Aiken, C. E.
Abstract: Aim: Complications of gestational diabetes (GDM) can be mitigated if the diagnosis is recognized. However, some at‐risk women do not complete antenatal diagnostic oral glucose tolerance testing (OGTT). We aimed to understand reasons contributing to non‐completion, particularly to identify modifiable factors. Methods: Some 1906 women attending a tertiary UK obstetrics centre (2018–2019) were invited for OGTT based on risk‐factor assessment. Demographic information, test results and reasons for non‐completion were collected from the medical record. Logistic regression was used to analyse factors associated with non‐completion. Results: Some 242 women (12.3%) did not complete at least one OGTT, of whom 32.2% ( n  = 78) never completed testing. In adjusted analysis, any non‐completion was associated with younger maternal age [≤ 30 years; odds ratio (OR) 2.3, 95% confidence interval (CI) 1.6–3.4; P  < 0.001], Black African ethnicity (OR 2.7, 95% CI 1.2–5.5; P  = 0.011), lower socio‐economic status (OR 0.9, 95% CI 0.8–1.0; P  = 0.021) and higher parity (≥ 2; OR 1.8, 95% CI 1.1–2.8; P  = 0.013). Non‐completion was more likely if testing indications included BMI ≥ 30 kg/m 2 (OR 1.7, 95% CI 1.1–2.4; P  = 0.009) or family history of diabetes (OR 2.2, 95% CI 1.5–3.3; P  < 0.001) and less likely if the indication was an ultrasound finding (OR 0.4, 95% CI 0.2–0.9; P  = 0.035). We identified a common overlapping cluster of reasons for non‐completion, including inability to tolerate test protocol (21%), social/mental health issues (22%), and difficulty keeping track of multiple antenatal appointments (15%). Conclusions: There is a need to investigate methods of testing that are easier for high‐risk groups to schedule and tolerate, with fuller explanation of test indications and additional support for vulnerable groups. What's new?: Gestational diabetes is associated with significant complications if untreated, yet a proportion of at‐risk women invited for antenatal screening do not complete testing. There is a lack of evidence to guide improvements in antenatal screening completion. Younger women and those from minority ethnic groups were less likely to complete testing. Key barriers to completion cited by women related to the demands of the testing protocol, ability to attend appointments, and mental health or social issues. Modification of testing protocols, increased support for vulnerable groups, and fuller explanation regarding test indications and risk could improve screening rates.